2013
DOI: 10.1177/0951629813505724
|View full text |Cite
|
Sign up to set email alerts
|

Executive appointments: Duration, ideology, and hierarchy

Abstract: While contemporary scholars generally view the Senate’s nominee approval role as impacting bureaucratic capacities and the president’s ability to realize campaign pledges, empiricists and theorists focus on different elements of bargaining. Since empiricists typically study confirmation delays, and theorists normally analyze equilibrium nomination preferences, theory and data rarely inform one another. We remedy this by specifying an executive appointment model jointly incorporating delays and appointee ideol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 39 publications
3
35
0
Order By: Relevance
“…Intuitively, this may suggest that high‐level nominations such as cabinet secretaries are more difficult to delay, whereas the lowest‐level nominees may not be valuable enough to delay for reasons of policy. The data trend also comports well with the intuition of Chiou and Rothenberg () about the relative costs of delay by position. While seemingly more innocuous, delay of such midlevel appointments is still likely to hamper agency performance and disrupt executive control over policy implementation by creating “neckless” bureaucracies (Light ).…”
Section: Investigating Strategic Delaysupporting
confidence: 86%
See 2 more Smart Citations
“…Intuitively, this may suggest that high‐level nominations such as cabinet secretaries are more difficult to delay, whereas the lowest‐level nominees may not be valuable enough to delay for reasons of policy. The data trend also comports well with the intuition of Chiou and Rothenberg () about the relative costs of delay by position. While seemingly more innocuous, delay of such midlevel appointments is still likely to hamper agency performance and disrupt executive control over policy implementation by creating “neckless” bureaucracies (Light ).…”
Section: Investigating Strategic Delaysupporting
confidence: 86%
“…Examples of such offices include major independent regulatory board positions and higher‐ranking agency officials. When considering delaying a nominee, however, the temptation to delay high‐ranking nominees is likely to be tempered with the increased risk associated with a more visible display of obstruction (Chiou and Rothenberg ). As such, midlevel nominations may be targeted due to the combination of a lower profile and substantial policy influence.…”
Section: Obstruction and Executive Nominationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent studies have noted that delay is endemic to the Senate nominations process (Chiou and Rothenberg 2013;McCarty and Razaghian 1999;O'Connell 2009) and furthermore that such delay is a leading cause of failure for nominees (Bond et al 2009). Furthermore, Corley (2006) has demonstrated that presidents are more likely to use their recess appointment powers in the face of senatorial delay, which implies that presidents have been using this power in instances of controversy or disagreement.…”
Section: Recess Appointmentsmentioning
confidence: 97%
“…In addition, Chiou and Rothenberg (2014) note that, as high-ranking positions are the most high profile, confirmation delay comes with potential audience costs for legislators; conceivably, Presidential delay when nominating might risk the same backlash for the most high-profile and high-ranking positions. 4 Therefore, the incentive to affect policy by quickly replacing higher-ups leads to a second hypothesis.…”
Section: Theory and Hypothesesmentioning
confidence: 99%